PEMANDUAN MANAJEMEN TAMAN PENDIDIKAN AL-QUR’AN(TPA)DI MASJID AROFAH, DUSUN BANDUNG DAN DUSUN SONGBANYU 1,KECAMATAN SONGBANYU, GUNUNG KIDUL,DAERAH ISTIMEWA YOGYAKARTA - Muntoha Muntoha (Asian Journal of Innovation and Entrepreneurship, 2015)
Taman Pendidikan Al-Qur'an (abbreviated as TPA or TPQ) is a body or group ofpeople who organize non-formal type of Islamic education which aims to provide teachingof reading Al-Qur'an at an early age, as well as understand the kindergarter-aged children-based basics of Islam, elementary school or madrasah (SD/MI) or even higher. Broadlyspeaking, the landfill useful for teaching Al-Qur’an in the form of reading, writing, and basicunderstanding of its interpretation. Teaching system is created to focus and fun inaccordance to children. So, a good managementsystem is the key to successing learningin a TPA. Unfortunately, this does not happen in a TPA at Arofah Mosque, Dusun BandungDan Dusun Songbanyu 1, Kecamatan Songbanyu, Gunung Kidul, Daerah IstimewaYogyakarta. Bad management, one teacher, and the absence of regeneration are mainproblems. Based on this, author took the initiative to do theguidingand supporting toorganizea good and integrated TPA management. With this guidance and support, theTPA will run better and organized. Slowly, Dusun Bandung and Dusun Songbanyu 1 willfeel a greater benefit from the presence of theTPA.